The Role of Cadmium Induced EGFR/STAT5 Pathway Activation in Epithelial to Mesenchymal Transition - Aikaterini Stavrou; Angelica Ortiz; Max Costa (Current Innovations in Disease and Health Research Vol. 7, 2023)
Cadmium (Cd) is a toxic and carcinogenic heavy metal found in cigarette smoke, air and drinking water, due to agricultural and industrial activities, posing a health risk to the general population. Prolonged, low-dose Cd exposure via inhalation or ingestion induces lung and kidney cancers in both humans and animal models. While exposure to high-dose Cd is cytotoxic and is correlated with the occupational setting, low-dose Cd exposure is carcinogenic and predominantly correlated with the general population. Even though Cd is categorized as a group 1 “human carcinogen” by IARC, the mechanism by which Cd-exposed cells overcome calcium chelation and induce malignant transformation remains unclear. This study examines the mechanism by which cells exposed to low doses of Cd survive the loss of E-cadherin cell-cell adhesion and induce epithelial-to-mesenchymal transition (EMT). Two epithelial cell lines, BEAS-2B and HEK293, were exposed to 0.4 µM and 1.6 µM of Cadmium chloride hemipentahydrate (CdCl2.2.5H2O) for 24 hours (h) and 9 weeks (wks). The chosen doses are environmentally relevant to levels of Cd found in food and cigarettes. A dose-dependent decrease in E-cadherin and an increase in N-cadherin protein expression was observed in cells treated with low-dose Cd. Moreover, Cd treated cells exhibited a faster proliferation rate when compared with control cells. This observation led to the examination of the EGFR/STAT5 pathway activation, which has also been observed to be activated in studies done in cancer cells. Our results showed a dose-dependent and time-dependent increase in both total EGFR and phosphorylated EGFR (p-EGFR) protein. Similar results were observed with STAT5 and phosphorylated STAT5 (pSTAT5) protein in both short-term and long-term exposures, however the 0.4 µM dose had the highest expression at 24 h. EGFR/STAT5 inducible genes were also upregulated in Cd-treated cells in just 24 h. These data demonstrate that epithelial cells can overcome Cd-mediated toxicity by activating the EGFR/STAT5 pathway to induce cell survival and proliferation, leading to EMT.